Pacientes con diagnóstico de hipertrofia prostática benigna atendidos por consulta externa en HTD desde mayo del 2011 hasta mayo del 2012. - Gia Estrada, Jimmy G. (2012)
This research work was conducted during may 2011 to may 2012 in the urology area of Teófilo Dávila Hospital by filling in question forms with 94 patients that came to the hospital with symptoms of benign prostatic hypertrophy cord were operated.